2018
DOI: 10.1128/msystems.00108-17
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Selection at Drug Resistance Loci in Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), is a significant burden on global health. Antibiotic treatment imposes strong selective pressure on M. tuberculosis populations. Identifying the mutations that cause drug resistance in M. tuberculosis is important for guiding TB treatment and halting the spread of drug resistance. Whole-genome sequencing (WGS) of M. tuberculosis isolates can be used to identify novel mutations mediating drug resistance and to predict resistance patterns fast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 65 publications
4
48
0
Order By: Relevance
“…We did not detect an effect of purifying selection on inference of migration in our three population simulation analyses (Appendix S2, Figures S13 and S14), but differences in the strength of purifying selection could contribute to the lineage-specific differences we observed in the size of inferred population expansions: i.e., genome-wide patterns of purifying selection could differ among lineages. Previous evidence has suggested that the fitness trade-offs of drug resistance mutations vary among lineages (Mortimer, Weber, & Pepperell, 2018), making this intriguing possibility potentially feasible.…”
Section: Lineage and Region Specific Patterns Of Migrationmentioning
confidence: 99%
“…We did not detect an effect of purifying selection on inference of migration in our three population simulation analyses (Appendix S2, Figures S13 and S14), but differences in the strength of purifying selection could contribute to the lineage-specific differences we observed in the size of inferred population expansions: i.e., genome-wide patterns of purifying selection could differ among lineages. Previous evidence has suggested that the fitness trade-offs of drug resistance mutations vary among lineages (Mortimer, Weber, & Pepperell, 2018), making this intriguing possibility potentially feasible.…”
Section: Lineage and Region Specific Patterns Of Migrationmentioning
confidence: 99%
“…The use of genomic data to detect homoplasy events is not an uncommon scientific technique [52][53][54]. In Mycobacterium tuberculosis, it is a well-known method to identify advantageous mutations, as they are likely to be associated with phenotypes such as drug resistance, heightened transmissibility, or host adaptation [12][13][14][15]. A similar approach was taken recently by Benjak et al to screen for highly polymorphic genes and genomic regions of Mycobacterium leprae [55].…”
Section: Discussionmentioning
confidence: 99%
“…One can use the Consistency Index to recognize genomic locations subjected to homoplasy, and relate the single-nucleotide polymorphism (SNP) positions that are inconsistent with the phylogeny to antibiotic resistance, as has e.g. been done in multiple studies on Mycobacteria spp [12][13][14][15].…”
mentioning
confidence: 99%
“…Sulfamethoxazole has been the first-line antibiotic agent against Stenotrophomonas for decades and is widely use in agriculture. The usage of specific antibiotic agent has been shown to result in purifying selection in certain genes of resistant strains ( Mortimer et al, 2018 ), because purifying selection on a subset of genes can be intensified in the setting of resistance. After sufficiently long-term usage of the same antibiotic agent, resistance may even reach a point of stabilizing evolution, completely reducing or invaliding the efficiency of the drug ( Cornick et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%